Excel 2019 for dummies - Harvey, Greg (--For dummies., 2018)
The bestselling Excel book on the market -- now in a new edition covering the latest version of Excel! Excel is the spreadsheet and data analysis tool of choice for people across the globe who utilize the Microsoft Office suite to make their work and personal lives easier. It is estimated that 1 in 7 people on the planet use Microsoft Office! If you're one of them, and want to get up to speed on the latest changes in Excel, you've come to the right place. Excel 2019 For Dummies has been updated to reflect the major changes and features made to Excel and covers everything you need to know to perform any spreadsheet task at hand. It includes information on creating and editing worksheets, formatting cells, entering formulas, creating and editing charts, inserting graphs, designing database forms, adding database records, using seek-and-find options, printing, adding hyperlinks to worksheets, saving worksheets as web pages, adding existing worksheet data to an existing webpage, pivot tables, pivot charts, formulas and functions, Excel data analysis, sending worksheets via e-mail, and so much more! Get to know the new Excel interface Become a pro at the spreadsheet and data analysis tool that's available as part of the Microsoft Office suite Find time-tested and trusted advice from bestselling author and expert Greg Harvey Use Excel to streamline your processes and make your work life easier than ever before Written by a bestselling author and seasoned educator, Excel 2019 For Dummies makes it easier than ever to get everything out of this powerful data tool.